THE MAIN TRENDS IN CHANGES OF EDUCATING TEACHERS - BUDZEN, Henryk (Trends in education, 2010)
Educational, training and development system should provide appropriate preparation for teachers to realize their professional functions as well as to include new trends in education of people. The need of changes in educational, training and development system are justified in lack of sufficient preparation which is emphasized by professional teachers. Due to the facts mentioned the article aims to substantiate a thesis that changes in educating teachers are needed and proposes the course of those changes.
Keywords: educating; training; development; teachers; course of changes.